(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the ways to solve cognitive tasks in preschool education and creative thinking by giving students cognitive tasks in educational play activities, a deeper understanding of the nature of the issues studied, the formation of worldviews.